2019
DOI: 10.4103/jispcd.jispcd_409_18
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of maximum standardized uptake value of 18 F-flourodeoxy glucose positron emission tomography-computed tomography in head and neck cancer patients undergoing chemoradiotherapy

Abstract: Aims and Objectives: This retrospective study aims at correlating the pre- and post-therapy maximal standardized uptake values (SUV max ) of the whole-body 18-flourodeoxy glucose positron emission tomography (FDG-PET) scan with tumor response in patients with head and neck squamous cell cancer undergoing chemoradiotherapy. Materials and Methods: Data for this retrospective study were taken from the clinical records of 20 evaluable head and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In an earlier retrospective study on locally advanced head and neck cancer patients from India Srinivas et al . [ 20 ] failed to identify a cut-off value for pretherapy SUV max that could predict the probable outcome of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier retrospective study on locally advanced head and neck cancer patients from India Srinivas et al . [ 20 ] failed to identify a cut-off value for pretherapy SUV max that could predict the probable outcome of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in this study, the SUV max-P cut-off of 13.55 did not have any major bearing on the response rates or long-term survival outcomes, but the SUV max-N had a bearing on the outcomes. In an earlier retrospective study on locally advanced head and neck cancer patients from India Srinivas et al [20] failed to identify a cut-off value for pretherapy SUV max that could predict the probable outcome of therapy.…”
mentioning
confidence: 99%
“…Of note, none of the previously reported cases had documented RANBP2-ALK fusion. The high SUVmax (Figure 3) value on repeat examination is indicative of high glucose transporter-1 expression, which is also indicative of poor prognosis and radioresistance among a variety of malignancies (10)(11)(12)(13). Failure to accurately delineate the treatment volume is unlikely as the pre-treatment 18 F-FDG PET-CT has been employed in the treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…PET-CT is considered as the gold standard in detecting distant metastatic disease and may also detect second primary cancers in the lung or bowel. 77 Goel et al highlighted that PET-CT has a high sensitivity (92%) and specificity (95%) for the detection of distant metastasis in patients with suspected recurrent HNSCC. 78 Chen et al demonstrated the use of PET-CT in detecting involved retropharyngeal nodes in cases of NPC.…”
Section: Early Screening and Detection Of Omsmentioning
confidence: 99%
“…PET‐CT is considered as the gold standard in detecting distant metastatic disease and may also detect second primary cancers in the lung or bowel 77 . Goel et al .…”
Section: Early Screening and Detection Of Omsmentioning
confidence: 99%